2016
DOI: 10.1530/erc-16-0041
|View full text |Cite
|
Sign up to set email alerts
|

AIP mutations impair AhR signaling in pituitary adenoma patients fibroblasts and in GH3 cells

Abstract: Germline mutations in the aryl hydrocarbon receptor-interacting protein (AIP) gene predispose humans to pituitary adenomas through unknown molecular mechanisms. The best-known interacting partner of AIP is the aryl hydrocarbon receptor (AhR), a transcription factor that mediates the effects of xenobiotics implicated in carcinogenesis. As 75% of AIP mutations disrupt the physical and/or functional interaction with AhR, we postulated that the tumorigenic potential of AIP mutations might result from altered AhR s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 40 publications
0
16
0
2
Order By: Relevance
“…1), was unexpected. One possibility is that environmental factors interfere with pituitary tumorigenesis (Crabbe et al 1999), especially as the privileged molecular partner of AIP is the xenobiotic receptor AhR (aryl hydrocarbon receptor) (Carver et al 1998, Lecoq et al 2016. Alternatively, the phenotypic discrepancy could be related to greater genetic homogeneity due to additional backcrosses since the initial publication (F16 + 1-3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1), was unexpected. One possibility is that environmental factors interfere with pituitary tumorigenesis (Crabbe et al 1999), especially as the privileged molecular partner of AIP is the xenobiotic receptor AhR (aryl hydrocarbon receptor) (Carver et al 1998, Lecoq et al 2016. Alternatively, the phenotypic discrepancy could be related to greater genetic homogeneity due to additional backcrosses since the initial publication (F16 + 1-3).…”
Section: Discussionmentioning
confidence: 99%
“…AIP protein is ubiquitously expressed and is physiologically present in somatotroph and lactotroph cells, in association with the secretory vesicles, suggesting a potential role in hormone secretion. However, the precise molecular mechanisms by which AIP mutations lead to pituitary adenomas remain unclear (Lecoq et al 2016). Homozygous Aip knockout mice are not viable and die during embryonic development with various cardiovascular malformations (Lin et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A most recent study in fibroblasts from patients with four different AIP mutations showed that AhR expression was unaffected but that AhR target genes, i.e. CYP1B1 , AhR repressor ( AHRR ), were either reduced or increased depending on the AIP variant [52]. From a clinical viewpoint, patients carrying AIP mutations are more often young, male and with large GH- or mixed GH- and prolactin-secreting tumors [48, 53, 54].…”
Section: Discussionmentioning
confidence: 99%
“…3 El gen AIP tiene un tamaño de 8.080 pares de bases, contiene 7 exones (3 de ellos con variantes de secuencia denominados como a, b,c para los exones 1, 3 y 5) (figura 1a), da origen a un transcripto primario (ARN) que tiene 5 alternativas de splicing: corte de intrones y empalme de exones (figura 1b) con al menos 2 exones en cada una, sin embargo aunque se han reportado 4 isoformas del péptido, a la fecha tan solo se ha aceptado un único péptido funcional. 5 Las mutaciones en este gen se asocian con inestabilidad del AhR, 3,6 favoreciendo su degradación mediada por el sistema ubiquitina proteosoma 7 y/o alterando su actividad transcripcional, 8 con disminución de la actividad y señalización de la subunidad Gαi de receptores asociados con proteínas G triméricas, 9 menor actividad y bajos niveles de fosfodiesterasa PDE4A5. 10 Hasta el momento se han reportado en la literatura 20 variantes patogénicas y 50 probablemente patogénicas del gen AIP (ClinVar diciembre 2018).…”
Section: N T Ro D U C C I ó Nunclassified
“…La hsp90 en sus aminoácidos 629 a 732 se une a la AIP a través de sus dominios TPR y en sus aminoácidos 272 a 617 se une al AhR. 8,11 Existen diversos conceptos acerca del efecto de la proteína AIP en la función del AhR, así por ejemplo, se ha considerado que su principal acción es proteger a AhR de la degradación proteosómica mediada por ubiquitinas. 7 El aumento en la expresión del AhR y el ARNT, varía según el tejido, estimulo o inhibición de la actividad transcripcional y los niveles de expresión del AhR.…”
Section: Interacciones Destacadas De Aipunclassified